Anti-inflammatory effect of rain tree leaf extract gel (Samanea saman) on fibronectin expression: study experimental - Sa'adah, Nikmatus; Veronica, Silvia; Prehananto, Herlambang; Kusumastuti, Endah; Gustina, Mara; Lukis, Prima Agusti; Adriansyah, Agus Aan; Abd Ghafar, Siti Aisyah (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRACT  Introduction: A traumatic ulcer is an open wound on the skin or mucous membranes that often results from trauma, such as scratches, bites, shocks, or pressure. Rain tree leaves (Samanea saman) have the potential to reduce pain and anti-inflammatory effects thanks to the flavonoid content. This extract works by inhibiting the cyclooxygenase and lipoxygenase pathways, which help limit inflammation and accelerate wound healing. This study aims to evaluate the effects of a 12% concentration rain tree leaf (Samanea saman) extract gel on fibronectin expression in the process of healing traumatic ulcers. Methods: This experimental laboratory study employed a post test only control group design. The sample consisted of male white rat wistar Rattus norvegicus and a gel of rain tree leaf extract extracted with a 98% ethanol solvent using a maceration method with a 12% concentration. Data analysis was performed using the Mann- Whitney U test. Results: The highest average was observed in the treatment group receiving the 12% rain tree leaf extract gel (Samanea saman), with an average value of 54.078, while the lowest average was found in the placebo gel control group, with a value of 22.462. Statistical analysis using the Mann-Whitney U test revealed a significant difference between groups (p = 0.004, p < 0.05). Conclusion: A 12% concentration of rain tree leaves (Samanea saman) extract gel significantly enhances fibronectin expression, contributing to the healing process of traumatic ulcers. KEY WORDS: Traumatic ulcers, fibronectin, rain tree leaf extract gel (Samanea saman), wound healing process. Antiinflamasi gel ekstrak daun trembesi (Samanea saman) terhadap ekspresi fibronektin: studi eksperimental ABSTRAK Pendahuluan: Ulkus traumatikus adalah luka terbuka pada kulit atau mukosa yang sering disebabkan oleh trauma seperti goresan, gigitan, benturan, atau tekanan. Daun trembesi (Samanea saman) memiliki potensi mengurangi nyeri dan efek anti-inflamasi berkat kandungan flavonoid. Ekstrak ini bekerja dengan menghambat jalur siklooksigenase dan lipooksigenase, yang membantu membatasi peradangan dan mempercepat proses penyembuhan luka. Tujuan penelitian ini untuk mengetahui peranan gel ekstrak daun trembesi (Samanea saman) dengan konsentrasi 12 % terhadap ekspresi fibronektin pada proses penyembuhan ulkus traumatikus. Metode: Eksperimental laboratoris dengan desain penelitian post test only control group. Sampel menggunakan hewan coba tikus putih jantan wistar Rattus norvegicus dan gel ekstrak daun trembesi yang diekstraksi dengan pelarut etanol 98% menggunakan metode maserasi dengan konsentrasi 12 %. Analisis data menggunakan uji Mann- Whitney U. Hasil: Rata-rata tertinggi ditemukan pada kelompok perlakuan yang menerima gel ekstrak daun pohon trembesi 12% (Samanea saman), dengan nilai rerata sebesar 54,078, sedangkan rata-rata terendah ditemukan pada kelompok kontrol gel plasebo, dengan nilai sebesar 22,462. Uji Mann-Whitney U menunjukan bahwa terdapat perbedaan yang signifikan dengan nilai signifikan n 0,00 < 0,05. Simpulan: Pemberian gel ekstrak daun trembesi (Samanea saman) 12% berpengaruh terhadap ekspresi fibronektin pada proses penyembuhan ulkus traumatikus. KATA KUNCI: Ulkus Traumatikus, fibronektin, gel ekstrak daun trembesi (Samanea saman), proses penyembuhan luka.